Levantamento de Leguminosae arbóreas do corredor de biodiversidade Santa Maria PR e germinação de sementes de Mimosa bimucronata (DC.) Kuntze - Marcon, Thaís Regina (2013)
Leguminosae Juss. is the third largest family of Angiosperms, comprising 727 genera and 19,325 species. Due the great N2 fixation in the soil, this family represents one of the leading families in floristic, phytosociological studies and recovery projects of degraded areas. However, some of these species have dormancy, which hinders germination. Such species variety can lead to difficulties in identification, particularly in sterile sample collection. Therefore this study aimed to develop a list with field tips, systematic identification keys and an illustrated guide, addressing the major vegetative diagnostic features of Leguminosae arboreal of Corredor de Biodiversidade Santa Maria, PR; as well as evaluate the germination test and treatments to overcome Seed dormancy of 10 Mimosa bimucronata (DC.) Kuntze. Samples have been collected in different areas of the Corridor. Legumes collected were photographed, recording morphological and vegetative stem rhytidome, staining the inner bark and / or sapwood, presence of gum shape of the leaflets, the presence of spines, glands, hairiness, and when present, flower and fruit. The samples were identified and housed into the Herbario da Universidade Estadual do Oeste do Paraná. For breaking dormancy were tested different treatment and also performed curve soaking to these seeds. Was prepared with a list of 29 tips field Leguminosae species found in the study area, which were made for one dichotomous key and a guide with plates illustrating the main diagnostic vegetative characteristics in order to assist in the identification of species of Leguminosae present in West of Paraná. The treatments with higher germination percentage and better germination speed were: immersion in sulfuric acid (10 min); soaking in acetone for 15 min, cutting the integument and immersion in water at 80oC (cooling in 24 hours), being the latter the most indicated. But all are efficient to overcome dormancy of M. bimucronata by increasing the percentage of germinated seeds and germination rate